SPORTS STUDY OF FOOTBALL IN KARANGANYAR DISTRICT - Nuruddin Priya Budi Santoso; Shodiq Hutomono; Aji Winata, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2022)
The aims of this research are: (1) To find out the facilities and infrastructure for football sports in Karanganyar Regency. (2) Football sports development system in Karanganyar Regency. (3) The role of the Regional Government in sports in Karanganyar Regency. (4) Achievements that have been achieved by the sport of football in Karanganyar Regency. The method used in this research is descriptive qualitative. The data source was obtained from the Football School Club in Karanganyar district. Data collection techniques using observation, interviews and documentation. Based on the results of data analysis: (1) Sports facilities andinfrastructure in Karanganyar district. The increase in football performance in Karanganyar district through the regional government has also been improved by revitalizing the football stadium in Karanganyar. (2) The football sports coaching system has been proven where KONI Karanganyar Regency collaborates with related parties to expedite and make the sports coaching program more effective, one of the streamlining of the Education Department's collaboration program in terms of nursery and early childhood development, through activities such as PORSENI, POPDA. (3) The role of the district government in football. Participation in the development and development of football sports achievements through KONI Karanganyar district, that the Regent of Karanganyar issued a policy that the Regent promote sports in Karanganyar, especially football by revitalizing the stadium. (4) The achievements achieved by football in Karanganyar Regency, data was found that the club with the highest achievement was the Zettle Meyer football club, proven by the results of interviews with administrators, coaches and athletes of the Zettle Meyer club that the club won the Surakarta National Football Championship and won the National Cross Championship. Nusantara CentralJava Governor's Cup.